MANUFACTURING COMPANY'S STOCK PRICE: EFFECTDIVIDEND PER SHARE, EARNING PER SHARE, RETURN ON INVESTMENT, PRICE BOOK VALUE LISTINGIN BEI - Titin Eka Ardiana; Ika Farida Ulfah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The increase in stock prices is strongly influenced by dividends per share, earnings per share, return on investment, and price book value. The data collection technique in this study uses financial report data from all manufacturing companies listed on the Indonesia Stock Exchange in 2018, which are 131 companies and uses a purposive sampling technique. The results of this study both partially and simultaneously show that Dividend Per Share (DPS) has an influence on stock prices which can explain that the greater the dividends distributed by the company, the direct impact on the increase in the company's share price. 2) There is a significant effect of Earning Per Share (EPS) on stock prices. 3) The negative effect of Return on Investment (ROI) on stock prices illustrates that the profit information obtained by the company for each company's total assets is not necessarily responded to by investors with high stock prices. 4) The influence of Price Book Value (PBV) indicates that the value of the company perceived by investors will be in line with the increase in the company's stock price. The contribution of the four dependent variables to stock prices is 86.8% and 3.2% can be explained by other variables outside of this study. Keywords: Share Price, Dividend Per Share (DPS), Earning Per Share (EPS), Return on Investment (ROI), Price to Book Value (PBV)